Giant cell arteritis of myometrial and axillary arteries and polymyalgia rheumatica. Issue 3 (March 1987) - Kyle, V; Dutoit, S H; Elias-Jones, J; Hazleman, B
Abstract : Giant cell arteritis (GCA) of the uterus and adnexa is extremely rare–only nine cases have been reported. We report a further case, in which the patient was found to have GCA of the myometrial arteries on routine hysterectomy. She then developed another rare manifestation of GCA, involvement of the axillary arteries causing arm claudication and chronically ischaemic hands.